The influence of hybrid work and work-life balance on the performance of PT. Tuest tech Indonesia employees - Syamsul Bachri; Riyandi Nur Sumawidjaja; Yoyo Sudaryo; Mochammad Mukti Ali; Erna Herlinawati; Dadan Abdul Aziz (Sean Institute, 2024)
The purpose of this study was to analyse the relationship less than optimal performance of the employee influence working environmental condition either directly or indirectly that is, have not carried out their service duties optimally. This condition is caused by most employees in the environment of PT.Truest Tech Indonesia on average have a low hybrid working background, and low work-life balance to carry out tasks and responsibilities, so that the process of providing services to customers encounters many obstacles. Aspects of hybrid working, and work-life balance are increasingly important and urgent in improving the quality of employees or employees in order to have the ability to influence the effectiveness of service to customers which is very pervaded by various ignorance, low performance, decreased productivity and quality. The purpose of this study is to describe hybrid working, work-life balance and performance as well as to analyse the influence of hybrid working, and work-life balance on employee performance. The method used is descriptive survey method and explanatory survey. The type of investigation in this study is causality. The unit of analysis of the employees of PT. Truest Tech Indonesia with a population of 100 employees. The time horizon in this study is cross sectional and the analytical methods used are frequency distribution and path analysis.